2007
DOI: 10.1002/pros.20555
|View full text |Cite
|
Sign up to set email alerts
|

ErbB‐4 may control behavior of prostate cancer cells and serve as a target for molecular therapy

Abstract: High expression of ErbB-4 in prostate cancer Cl-1 cell clones correlated with high proliferative and migration capacity and high tumorigenic potential. The inhibitory effect of Mab on cell proliferation and on subcutaneous tumor growth suggests ErbB-4's potential as a target for molecular anticancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…A few studies have analyzed the role of HER4 receptor in PCa, and the conclusions are controversial. Some investigators have correlated the expression of HER4 with enhanced prostate cell proliferation and migratory capacity (64,65), but others have reported that HER4 has a tumor-suppressive effect (66,67). HER4 activity has also been related to acquired resistance to anti-EGFR therapies, as the signaling through the PI3K/Akt survival pathway can be alternatively activated by HER4 (39).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have analyzed the role of HER4 receptor in PCa, and the conclusions are controversial. Some investigators have correlated the expression of HER4 with enhanced prostate cell proliferation and migratory capacity (64,65), but others have reported that HER4 has a tumor-suppressive effect (66,67). HER4 activity has also been related to acquired resistance to anti-EGFR therapies, as the signaling through the PI3K/Akt survival pathway can be alternatively activated by HER4 (39).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our earlier findings, 17 we selected two clones of Cl-1 cells: clone #3 and clone #7. The highly proliferative clone #3 had high ErbB4 expression and the low proliferative clone #7 had low ErbB4 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies 17,18 revealed that overexpression of ErbB4 is present in 38% of prostate cancer patients and that targeting ErbB4 receptor in in vivo and in vitro using an androgen-resistant cell line is an effective treatment approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The ability of ERBB4 antibodies to slow the growth of several prostate cancer cell lines in vitro and in mouse xenograft models suggests that this gene may possess biological activity in prostate tissue. 13 Therefore, in contrast to other epithelial tumors, the prostate may be a site in which ERBB4 function could be targeted as an anti-cancer therapy. The role of ERBB4 in promoting cell growth, however, remains controversial as high protein expression correlates to an extended time to relapse in hormone-sensitive prostate tumors 12 and ERBB4 overexpression induces prostate cancer cells to growth arrest.…”
mentioning
confidence: 99%